Are They Calling My Name? Attention Capture Is Reflected in the Neural Tracking of Attended and Ignored Speech - Holtze, Björn; Jaeger, Manuela; Debener, Stefan; Adiloğlu, Kamil; Mirkovic, Bojana (Frontiers in Neuroscience, 2021)
Difficulties in selectively attending to one among several speakers have mainly been associated with the distraction caused by ignored speech. Thus in the current study, we investigated the neural processing of ignored speech in a two competing-speaker paradigm. For this, we recorded the participant’s brain activity using electroencephalography (EEG) to track the neural representation of the attended and ignored speech envelope. To provoke distraction, we occasionally embedded the participant’s first name in the ignored speech stream. Retrospective reports as well as the presence of a P3 component in response to the name indicate that participants noticed the occurrence of their name. As predicted, the neural representation of the ignored speech envelope increased after the name was presented therein, suggesting that the name had attracted the participant’s attention. Interestingly, in contrast to our hypothesis, the neural tracking of the attended speech envelope also increased after the name occurrence. On this account, we conclude that the name might not have primarily distracted the participants, at most for a brief duration, but that it alerted them to focus to their actual task. These observations remained robust even when the sound intensity of the ignored speech stream, and thus the sound intensity of the name, was attenuated.